Biochemical Markers of Early Renal Dysfunction in Patients with β-thalassemia Major: A Systematic Review and Meta-analysis - Arian, Mahdieh; Oghazian, Mohammad Bagher; Nour El Dine, Mohammad Hassan; Valinejadi, Ali; Badiee, Zahra; Soleimani, Mohsen; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2025)
BackgroundEarly diagnosis of renal dysfunction in β-thalassemia major (β-TM) may help take specific measures to delay irreversible damage and renal failure. Therefore, the present meta-analysis aimed to compare biochemical markers of premature renal dysfunction between β-TM and healthy subjects and identify renal issues' prevalence in patients with β-TM.MethodsWe searched PubMed, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Medline, Scopus, Web of Science, ScienceDirect, ProQuest, Google Scholar, and State Inpatient Databases (SIDs) without any language constraints for all relevant articles published up to April 2019.ResultsOut of 1458 articles published up to April 2019, 24 case-control and 22 cross-sectional studies were investigated. The investigated levels of serum phosphorus, uric acid (UA), cystatin C, and ferritin were significantly different between β-TM patients and controls. The albumin/creatinine ratio (ACR), N-acetyl-β-D-glucosaminidase/creatinine (NAG/Cr) ratio, urinary and serum β2 microglobulin (β2MG), and serum ferritin levels were significantly higher in β-TM patients than in healthy individuals. However, glomerular filtration rate, creatinine clearance, and pretransfusion hemoglobin indicated a significantly lower rate. The general prevalence of renal glomerular and/or tubular defects in patients with β-TM was 50.22%.ConclusionUrinary NAG, β2MG, ACR, and Scys-C may be early markers of renal dysfunction in patients with β-thalassemia major. An observation of elevated levels of these markers despite normal levels of other markers of renal dysfunction may indicate primary, subclinical injury to the renal tubules and glomeruli.
Keywords: urinary albumin/creatinine ratio